Understanding of disease severity of thalassemia. - Tao, Feng. (2009)
Thalassemia is an inherited autosomal recessive blood disease, which is caused by imbalanced expression of α and non-α hemoglobin subunits. Since quantitative relationship between globin chains is the major cause of disease, the severity of thalassemia disease is hypothesized correlated with quantities of hemoglobin subunits and the degradation efficiency of excess globins. In this study, absolute quantification of hemoglobin subunits was performed by using stable isotope labeled internal standards and mass spectrometry. Three different internal standards were successfully generated including: synthetic protein QconCAT, 15N labeled recombinant protein standards, and proteolytic 18O labeled peptides during trypsin digestion. From the experiment simplicity and result accuracy point of view, proteolytic 18O labeling was selected for this study. Seven different patients with disease severity from mild to severe were studied. The pattern demonstrated in this experiment, i.e. the lower the β to α globin concentration ratio the more severe the disease of β-thalassemia, implicates a correlation between the concentration ratios of β versus α globin and the disease severity. This newly proposed protocol for absolute quantification of human hemoglobin subunits in peripheral blood has been proved to be accurate, convenient as well as effective. Upon further development, it may serve as an intuitive and precise approach for thalassemia disease classifications, thereby can be the foundation for more accurate and faster diagnosis for β-thalassemia severity. The quantification of the hemoglobin subunits is measuring the result of equilibrium between protein synthesis and degradation. Up till now, the synthesis pathways of hemoglobin has been well-studied already.